Road Pavement Evaluation and Planning (International Conference of Graduate School on Sustainability (ICGSS), 2020)
The increasing number of population and high mobility has also raised the pressure for local stakeholders to fulfil the necessity of basic infrastructure (roads). Roads play crucial a role in a society as they are the necessary means in moving people, facilitating access to development, as well as in driving the economic growth of a community. The volume of road traffic will eventually influence the durability of roads. The higher volume of traffic a road experiences, the shorter service life spans the road will have.  This article reviewed previously existing studies regarding the evaluation, planning, and repairment method of concrete, paving, and asphalt pavement by utilising narrative review method. The review was conducted by scrutinising relevant body of literature. The findings suggest that the evaluation and repairment methods for road pavement vary.